Life-related negative customer emotions in real estate agent encounters - Lakkala, Hannamari (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The goal of this study was to explore how do customers’ life-related negative emotions affect real estate business. This was divided into two research questions: 1. What life-related negative emotions can be recognised in real estate customer encounters? 2. How do the recognised emotions affect customer encounters and the realtor’s work? 3. How can the realtor take the emotions into account in customer service? The theoretical background consists of two main lines of study: emotions and customer encounters. A wide literary review on emotions research was conducted from a cognitive psychology point of view, focusing on negative emotions. Emotions research was then combined into the field of customer encounters. Qualitative study was chosen as the methodological basis of the study. Empirical material of this study was collected through in-depth interviews with 13 successful Finnish real estate agents. Narrative research was used as a method for the study. Four life-related emotion categories were recognized in real estate customer encounters: sadness, anger, anxiety and shame. These emotions rose from issues varying from death of a close one to divorce and from major changes in life stages to deep emotional attachment to an old home. The study also found that these incidental negative emotions do affect customer encounters and realtors’ work. The emotions affected the decision making of customers and sometimes overshadowed reason. Some emotions made the customer passive and slow to make any decisions, while others made their decision making fast and hasty. Even though the incidental emotions might not have had anything to do with the real estate deal, they could affect the outcome of the customer encounter and the whole real estate deal. Interestingly enough, the study found that not all successful real estate agents knowingly serve customers in an emotional level. The study does, however, suggest that in fact it may be an ethical decision of the customer server to take into account the emotional state of the customer. Attending to the emotional side of customers does not only increase pleasantness of the customer encounter, but may improve and balance customer decision making and prevent hasty decisions possibly leading to improved customer satisfaction. This study also gave practical managerial implications to customer service providers on how negative incidental emotions can be attended to in a customer encounter. This study could be useful not only to real estate agents, but also in other types of customer service, especially with vulnerable populations or other types of home-related business.

Tutkimuksen tavoitteena oli tutkia kuinka asiakkaan omasta elämästä kumpuavat tunteet vaikuttavat kiinteistönvälitykseen. Tutkimusongelma jaettiin kolmeen tutkimuskysymykseen: 1. Mitä omasta elämästä kumpuavia negatiivisia tunteita voidaan tunnistaa kiinteistönvälitystapaamisessa? 2. Kuinka tunnistetut tunteet vaikuttavat kiinteistönvälitystapaamiseen? 3. Kuinka kiinteistönvälittäjä voi ottaa nämä tunteet huomioon työssään? Tutkimuksen teoriapohja kostuu kahden alan tutkimuksesta: tunteista ja asiakaskohtaamisista. Laaja kirjallisuuskatsaus tunnekirjallisuuteen tehtiin kognitiivisen psykologian näkökulmasta keskittyen negatiivisiin tunteisiin. Tunneteoria yhdistettiin liiketaloustieteen tutkimustuloksiin asiakaskohtaamisista. Tutkimuksen laajaksi lähestymistavaksi valittiin kvalitatiivinen tutkimus. Empiirinen materiaali kerättiin haastatteluissa 13 menestyneen suomalaisen kiinteistönvälittäjän kanssa. Narratiivinen tutkimus valittiin tutkimuksen kantavaksi tutkimusmetodiksi. Neljä asiakkaan elämästä kumpuavaa tunnekategoriaa tunnistettiin kiinteistönvälitystapaamisissa: suru, viha, pelko ja häpeä. Nämä tunteet nousivat monista taustoista vaihdellen läheisen kuolemasta avioeroon ja elämänvaiheen muutoksesta syvään tunnesiteeseen vanhaa kotia kohtaan. Tutkimus osoitti että kyseiset kiinteistönvälitykseen liittymättömät negatiiviset tunteet vaikuttivat kiinteistönvälitystapaamiseen ja jopa koko välityksen lopputulokseen. Tunteet vaikuttivat asiakkaan päätöksentekoon, joskus ohittaen järjen äänen. Jotkut tunteet passivoivat asiakasta ja tämän päätöksentekoa. Toiset taas kiirehtivät sitä. Vaikka tunteet eivät välttämättä liittyneet asuntokauppoihin tai asiakaspalveluun mitenkään, saattoivat ne silti sanella asiakastapaamisten ja koko kauppojen lopputuleman. Tutkimuksessa kävi ilmi, etteivät kaikki menestyneet kiinteistönvälittäjät tiedosta työskentelevänsä asiakkaan elämään liittyvien tunteiden kanssa. Tutkimus kuitenkin viittaa siihen, että asiakkaan tunnetaustan huomioonottaminen paitsi tekee tilanteesta miellyttävämmän, on mahdollisesti myös eettisesti rakentava valinta, sillä ottamalla huomioon asiakkaan tunteet, välittäjä voi pyrkiä varmistamaan asiakkaan päätöksenteon tasapainoisuuden. Hätäisten ja kaduttavien päätösten estäminen voi myös johtaa pitkällä tähtäimellä asiakastyytyväisyyteen. Tutkimus antoi myös käytännön ajatuksia ja työkaluja asiakaspalvelijoille, jotka haluavat tiedostaen kehittää tunnetaitojaan työssä, jossa asiakkaan omasta elämästä kumpuavat tunteet ovat pinnalla. Tutkimusta voidaan hyödyntää paitsi kiinteistönvälityksessä, myös muussa asiakaspalvelussa, etenkin herkkienasiakasryhmien kanssa tai kotiin liittyvässä liiketoiminnassa